A Green Recycling Process for Lead Refining Waste. Issue 24 (24th June 2020) - Morcali, Mehmet H.
Abstract: Nearly 80% of metallic lead is used in the production of lead battery over the world. There is a need for efficient extraction process in order to provide a sustainable production since lead has an importance in the economy. The aim of the study was to present a green recycling process for lead waste generated from lead refining process (i. e. Colcord process‐ copper removing method). The purpose was to obtain higher extraction yield with lower energy consumption to leach lead from the refining waste. For this purpose, the extraction experiments were studied in order to examine the following effects; particle size, lixiviant concentration, agitation speed, S/L ratio, reaction temperature, reaction time and the effect of common anion. Almost 99% lead extraction was achieved by using dilute ferric nitrate at 55 °C for 12 hours under ambient pressure condition. Furthermore, the addition of common ions was examined in order to increase the percentage of lead extraction. Unfortunately, the addition of common ions showed negative effect on lead extraction. The proposed green and sustainable chemical process played a significant role in lead waste recycling in terms of supporting secondary lead stock or demand. Abstract : A green leaching process was applied on lead refining waste which is already occurred in de‐coppering process, using a non‐hazardous lixiviant. Various reaction parameters were investigated in detail. Lead acid batteries, which has an important mission likes carrying energy one place to another, are produced from metallic lead and lead compounds as is well known. The green process may facilitate on further scaling‐up studies and encourages industrial application.